1996
DOI: 10.1172/jci118611
|View full text |Cite
|
Sign up to set email alerts
|

Urokinase is required for the pulmonary inflammatory response to Cryptococcus neoformans. A murine transgenic model.

Abstract: Urokinase (uPA) is hypothesized to provide proteolytic activity enabling inflammatory cells to traverse tissues during recruitment, and it is implicated as a cytokine modulator. Definitive evaluation of these hypotheses in vivo has previously been impossible because uPA could not completely and irreversibly be eliminated. This limitation has been overcome through the development of uPA-deficient transgenic mice (uPA Ϫ / Ϫ ). Using these mice, we evaluated the importance of uPA in the pulmonary inflammatory res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
139
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(149 citation statements)
references
References 43 publications
(37 reference statements)
7
139
0
Order By: Relevance
“…Another possibility is that uPA-deficient fibroblasts are unable to migrate into the fibrin injection sites. Indeed, several reports have demonstrated a reduced migration of cells derived from uPA-deficient mice, 6,58,59 however from histological assessment, there did not appear to be a difference in cellularity at the fibrin-injected site between the three mouse strains. Furthermore, in vitro studies showed a lack of enhanced collagen accumulation even when cells were within a fibrin matrix.…”
Section: Discussionmentioning
confidence: 79%
“…Another possibility is that uPA-deficient fibroblasts are unable to migrate into the fibrin injection sites. Indeed, several reports have demonstrated a reduced migration of cells derived from uPA-deficient mice, 6,58,59 however from histological assessment, there did not appear to be a difference in cellularity at the fibrin-injected site between the three mouse strains. Furthermore, in vitro studies showed a lack of enhanced collagen accumulation even when cells were within a fibrin matrix.…”
Section: Discussionmentioning
confidence: 79%
“…In addition to their direct involvement in the proteolytic (uPAR) and adhesive properties of cells, both pro-uPA (Gudewicz and Bilboa, 1987; Boyle et Fibbi et al, 1988;Del Rosso et al, 1992;Resnati et al, 1996;Gyetko et al, 1996;Degryse et al, 1999) and VN (Yebra et al, 1996;Kjùller et al, 1997;Stahl and Mueller, 1997;Carriero et al, 1999; directly stimulate cell migration. The interaction of uPAR with several integrins and the modulation of their function is an established fact; for example, the presence and the level of uPAR a ects the choice between adhesion on ®bronectin v. vitronectin, the internalization of ®brinogen or even the constitutive activation of MAP-K in certain cancer cells leading to cell proliferation Simon et al, 1996;Xue et al, 1997;Dumler et al, 1999;Aguirre Ghiso et al, 1999;Kusch et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…However, infiltration of inflammatory leukocytes, especially macrophages, neutrophils, and T lymphocytes, into Cryptococcus neoformans-infected lung is severely impaired in uPAdeficient mice [37], clearly suggesting a requirement for the uPAR-uPA-PAI system for leukocyte migration in certain conditions. Furthermore, neutrophil migration in vitro in the absence of complement is impaired in patients with paroxysmal nocturnal hemoglobinuria, some of whose leukocytes lack GPI-anchored protein [38], suggesting a possible importance for a GPI-anchored protein, uPAR, in this migration.…”
Section: Regulation Of Leukocyte Transendothelial Migration By the Upmentioning
confidence: 99%